2022
DOI: 10.19103/as.2022.0099.15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors affecting the composition and quality of cow’s milk

Abstract: This chapter reviews the genetic factors affecting the composition and quality of cow's milk. It starts by discussing how different breeds of cattle can affect the composition of milk. The chapter then goes on to examine milk proteins, genetic variants and post-translational modifications. It then discusses milk coagulation and other functional properties, before highlighting the genetic influence of fatty acids on minor milk components. The chapter also discusses using mid-infrared spectroscopy for genetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 126 publications
0
5
0
1
Order By: Relevance
“…In addition, a report from the Food and Agriculture Organization of the United Nations (FAO) pinpoints the importance of animal milk in the diets of children in populations with very low fat intakes and limited access to other animal source foods ( https://www.fao.org/dairy-production-products/products/milk-composition/en/ ). Association genetics identified many genomic regions influencing different phenotypes of milk composition, showing in particular a major effect of the imprinted gene DGAT1 (Diacylglycerol O-Acyltransferase 1) and caseins on total yields of milk, protein and fat ( Poulsen and Larsen, 2021 ). In addition, other candidate genes mostly affecting milk fat and protein content were shown to play a role in secretory functions in the mammary gland as well as mammary gland development ( Cui et al, 2014 ).…”
Section: Harnessing Livestock Resources For a Fuller Picture Of The I...mentioning
confidence: 99%
“…In addition, a report from the Food and Agriculture Organization of the United Nations (FAO) pinpoints the importance of animal milk in the diets of children in populations with very low fat intakes and limited access to other animal source foods ( https://www.fao.org/dairy-production-products/products/milk-composition/en/ ). Association genetics identified many genomic regions influencing different phenotypes of milk composition, showing in particular a major effect of the imprinted gene DGAT1 (Diacylglycerol O-Acyltransferase 1) and caseins on total yields of milk, protein and fat ( Poulsen and Larsen, 2021 ). In addition, other candidate genes mostly affecting milk fat and protein content were shown to play a role in secretory functions in the mammary gland as well as mammary gland development ( Cui et al, 2014 ).…”
Section: Harnessing Livestock Resources For a Fuller Picture Of The I...mentioning
confidence: 99%
“…The total and ionic calcium contents were found to greatly influence the acid-induced gelation and rennet-induced coagulation of bovine milk ( Hallén et al, 2007 ; Poulsen et al, 2013 ; Poulsen and Larsen, 2021 ). In this regard, milk samples carrying β-casein A1 contained higher calcium amount, especially ionic calcium in A1/A2 milk compared to A2/A2 milk and smaller casein micelle sizes ( Daniloski et al, 2022d ; Day et al, 2015 ; Jensen et al, 2012a ; Poulsen et al, 2013 ).…”
Section: The Impact Of the Casein Variants On Processing And Producti...mentioning
confidence: 99%
“…Compared to other caseins, the genetic variants of κ-casein have been most discussed and related to acid gelation and rennet coagulation of bovine milk ( Bijl et al, 2014a ; Bonfatti et al, 2010 ; Poulsen and Larsen, 2021 ). Different studies have found that the genetic polymorphisms of κ-casein might substantially affect the rennet-induced coagulation characteristics; milks containing κ-casein B variant were represented with a higher amount of κ-casein and smaller casein micelles, decreased curd firming time, and increased whey protein expulsion compared with milks carrying κ-casein A ( Bisutti et al, 2022 ; Gambra et al, 2013 ).…”
Section: The Impact Of the Casein Variants On Processing And Producti...mentioning
confidence: 99%
See 2 more Smart Citations